Development of the Tourism Industry Using Branding Strategies by Competitive Multimedia in the Digital Era Based on Community Empowerment - Kartinawati, Erwin; Fitriyadi, Farid; Indriastiningsih, Erna (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
In a dynamic and ever-evolving digital era, the tourism industry faces the challenge of adapting and innovating to maintain its appeal. In this context, an effective branding strategy becomes crucial. Using or utilising competitive multimedia is one of the keys to achieving this goal. This research investigates the potential for integration between branding strategies through competitive multimedia and community empowerment in developing the tourism industry. Results show that when applied appropriately, competitive multimedia can strengthen identity, increase visibility, and deepen visitors' emotional engagement with tourism destinations. However, some technical challenges must be overcome, especially regarding the quality of promotional content. To overcome the problem, the proposed solution involves local communities deeply understanding the region's cultural richness and uniqueness in content production. With adequate training and access to the appropriate tools, communities can create content that is not only high quality but also authentic and rich in local narratives. Thus, this approach improves branding quality and promotes inclusive and sustainable tourism development. The main conclusion from this research is that the combination of multimedia technology and community empowerment can be a cutting-edge strategy for branding and promoting the tourism industry in the current digital era.